Cloud Database Analysis of Instant Messaging Apps on Mobile Devices - Roland Szabo (Applied Sciences)
The purpose of this paper is to present the creation, challenges and difficulties of four utility apps to increase production on Android handheld devices. The motivation of creating the apps and the problems encountered during creation are highlighted. The first app is a fast emoji app for WhatsApp. The motivation for creating such an app is that usually phone users do not like to type too much; with this app, they can communicate with each other just by sending emojis. The second app is a standalone emoji sender app, which does the same thing as the previous app but uses its own database, not the WhatsApp database.